ANALISIS KETERAMPILAN MENYIMAK SISWA KELAS 4 DI SDN SINDANGSARI 03 KECAMATAN CIGEDUG KABUPATEN GARUT - Icha Lilis Indriani; Lutfi Asyari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Listening skill is one of the fundamental competencies in the learning process, especially at the elementary school level. This study aims to analyze the listening skills of grade 4 students at SDN Sindangsari 03, Cigedug  District, Garut Regency, West Java, Academic Year 2024/2025. A descriptive quantitative approach combined with a case study method was employed. Data were collected through a 16-item questionnaire covering aspects of oral text comprehension, ability to follow verbal instructions, concentration, and identification of key information. The study involved 106 students selected from 170 grade 4 students using simple random sampling. Results showed that the majority of students (66.0%) had moderate listening skills, 18.9% were in the high category, and 15.1% were in the low category. These findings highlight the need for more interactive and varied learning strategies involving audiovisual media, storytelling methods, and active student engagement to enhance listening skill in elementary schools.